A Literature Review of Factors Affecting the Efficiency of Undergraduate Student Admission Management: A Case Study of the Institute of Vocational Education: Northern Region 4 - Thongdee, Saptasorn; Chotpittayanon, Natnicha (Journal of Humanities and Social Sciences, Rajapruk University, 2025)
This study synthesized the body of knowledge related to the factors influencing the effectiveness of undergraduate student admission management, with a case study of the Institute of Vocational Education: Northern Region 4. The McKinsey 7S Framework was applied as an analytical lens to categorize and interpret findings. The literature was drawn from research articles and academic papers published between 2020 and 2025 in TCI Tier 2 journals and related referenced works. The results revealed that five major factors—shared values, strategy, systems, structure, and skills—collectively explained up to 84.70% of the variance in management effectiveness. The study also proposed policy and practical recommendations to enhance the institutional admission process in response to the digital transformation and societal shifts following emerging disease events.